APPLICATION OF U(2) ALGEBRAIC MODEL IN THE STUDY OF STRETCHING VIBRATIONAL SPECTRA OF C50 AND C84 FULLERENES - Ashim Kalyan; Rupam Sen; Joydeep Choudhury; Nirmal Kumar Sarkar; Ramendu Bhattacharjee
The Hamiltonian describing the stretching vibrational spectra of polyatomic molecules is calculated within the framework of vibron model by using the dynamical U(2) Lie algebra. Here every C-C bond of the molecule is replaced by a corresponding Lie algebra and finally the Hamiltonian is constructed considering the interacting Casimir and Majorana operators. The fundamental stretching vibrational energy levels of the carbon C50 and C84 clusters are then calculated using this Hamiltonian to fit the experimental results.
Keywords: Physics; Materials science